RESILIENSI PERSPEKTIF AL QURAN - Wahidah, Evita Yuliatul (JURNAL ISLAM NUSANTARA, 2018)
Resilience or flexibility is one of the terms in the field of psychology. Paradigm is based on the view that comes from the field of psychology or sociology about how a person's good children, adolescents, and adults recover from the downturn, trauma, or stress resulting from the problem being experienced. There are individuals who can survive and rise from negative situations. However, not a few individuals who fail to get out of these negative situations. While the Qur'an has a unique view of man, his pages contain divine guidance on the creation of man and the human nature either explicitly or implicitly (needing interpretation) and offering problem solving over all the probabilities of his life. Included in the resilience is the ability of the individual who does not succumb when faced with pressure and problems. Departing from the paradigm, the discussion of the resilience of the perspective of the Qur'an becomes interesting. In addition to seeing the method of Islamization of developing science, also to explore aspects of resilience in Islam based on the Qur'an and Hadith. The Resistance of the Qur'an's perspective is also to provide an alternative to the criticisms of modern psychology that break away from divine values.